Encouraging Private Biodiversity - Incentives for Biodiversity Conservation on Private Land - Peter Clough (New Zealand Government, The Treasury, 2000)
This report provides a literature review on the practical experience of measures in other countries with a similar legal background to New Zealand to give economic incentive to biodiversity conservation on private land. It examines the strengths and weaknesses of the measures and draws out their relevance to New Zealand. The measures identified can be broadly characterised as conservation management agreements and fixed period contracts between conservation agencies and individual landholders over defined areas of land; purchase of partial interests in land; purchase of freehold interest in land and subsequent management by a conservation agency or voluntary body; restricting landholder development rights and allowing them to trade residual entitlements; and establishing proprietary rights in wildlife products. It identifies some incentive measures not currently used in New Zealand that could be adapted for application here, such as the European Environmentally Sensitive Area (ESA) schemes, or the US Conservation Reserve Program (CRP). Such schemes have the distinct characteristic of offering on-going incentives, and an ability to change land use practices over a wider countryside than discrete reserve areas. Many of the incentive schemes reviewed (e.g. covenants, land purchase) effectively create new reserves set aside from damaging activities. But in the context of New Zealand's biodiversity, land set aside in this manner will not revert to natural biodiversity without provision for on-going management. The literature reviewed said little about the effectiveness of particular incentive schemes in enhancing biodiversity, beyond noting their participation rates. It reports on areas covered, land-cover conserved, and involvement of land-owners but gives little indication of what would have resulted in the absence of the incentives. This review also uncovered little detailed examination of the mechanisms for disbursing funds - lump sum grants, matching grants etc - which have different administrative and compliance costs, and different effects on the incentive created for leverage of private funds on public inputs. Finally, while some landowners will volunteer sites for conservation with little encouragement or simple reimbursement of additional costs incurred for conservation, the opportunity costs of forgoing income may deter owners from offering the best sites for conservation purposes. Financial incentive instruments are not the only means of encouraging biodiversity and need to be seen in a wider policy context.
Keywords: 330